Optimization of Logistics Processes in an Electric Vehicle Service Center - Dworak, Przemysław (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of the chapter is to examine the functioning of the Oslo-North service center owned by Tesla, with a focus on its impact on customer service quality and logistical efficiency. The study applied participatory observation and analysis of both internal and publicly available data covering the period from March to August 2021. The research revealed seasonal differences in service volumes, staffing challenges, and low efficiency in the auto detailing process, which proved to be the weakest link in the service chain. Research limitations include the case study’s individual character. The findings have practical applications in service work planning and human resource management, pointing to the need for reorganization and the implementation of new technological solutions. The social relevance of the study stems from the growing importance of post-sale services in shaping customer experience (UX). The article contributes to the literature by highlighting the relationship between service quality and customer purchasing decisions in the e-mobility sector.